A Rapid Procedure for Identification and Antifungal Susceptibility Testing of Yeasts From Positive Blood Cultures - Vecchione, Alessandra; Florio, Walter; Celandroni, Francesco; Barnini, Simona; Lupetti, Antonella; Ghelardi, Emilia (Frontiers in Microbiology, 2018)
The development of rapid diagnostic assays for the identification and analysis of antimicrobial resistance of fungal pathogens causing invasive mycoses is of utmost importance to reduce morbidity and mortality. We evaluated the performance of a novel rapid method directly applied to monomicrobial blood cultures from patients with bloodstream infection caused by yeast, including nine Candida species and three non-Candida yeast. For the rapid method herein developed, samples of positive blood cultures were transferred into serum separator tubes and treated with sodium dodecyl sulphate; the yeast layer was recovered and directly used for microbial identification by MALDI-TOF mass spectrometry and antifungal susceptibility testing by the Sensititre YeastONE Y010 panel. The results were compared with those obtained by the same assays applied to colonies isolated on solid media. Using a score value of 1.700 as cut-off for valid identification, the rapid method identified 66 of 124 (53.2%) isolates, all of which concordantly with the reference method. However, adopting a cut-off ≥1.300 and ≥4 consecutive repetitions of the same species in the list of matches would extend concordant identification to 107/124 (86.3%) samples. Importantly, antifungal susceptibility testing revealed essential agreement between the two methods for all the isolate/antifungal drug combinations tested, including misidentified and not identified isolates. Therefore, the method herein developed represents a valid alternative for antifungal susceptibility testing of yeast from positive blood cultures, yielding accurate and reliable results at least 24 h earlier than with the routine method, thus allowing clinicians to promptly streamline antifungal therapy.